Spatial Heterogeneity and the Wage Curve Revisited - Simonetta Longhi; Peter Nijkamp; Jacques Poot (European Regional Science Association (ERSA), 2004)
Most `wage curve' studies treat local labour markets as independent `islands' in the national economy. However, when a local labour market is in close proximity of other labour markets, a local shock that increases unemployment may not lead to lower pay rates if employers fear outward migration of their workers. Hence, the unemployment elasticity of pay will be greater, the more isolated the local labour market is. Wages are also expected to be higher in regions that interact strongly with other regions. These hypotheses are confirmed by means of an estimation of wage curves with data for 327 regions of western Germany over the period 1990-97. Key words: Unemployment, wage formation, spatial analysis, local monopsony, Germany JEL classification: J21, J30, R23
Keywords: J21; J30; R23; 330; Unemployment; wage formation; spatial analysis; local monopsony; Germany